BIO-MATRICONDITIONING BENIH DENGAN RIZOBAKTERI UNTUK MENINGKATKAN MUTU FISIOLOGIS BENIH SORGUM (Sorghum bicolor L.) - Sutariati, Gusti Ayu Kade; Khaeruni, Andi; Madiki, Abdul (Jurnal Agroteknos, 2011)
Rhizobacteria have been used for plant growth enhancement. The research was aimed on finding the best method of preplant seed treatment through seed invigoration plus rhizobacteria as biofertilizer to increase physiological quality of preplant sorghum seed. The research was undertaken in Agronomy Laboratory, Agriculture Faculty, Haluoleo University, Kendari Southeast Sulawesi. Research results showed that seed bio- matriconditioning with rhizobacteria was effective in enhancing seed quality of sorghum. The most effective treatment was the integration of seed matriconditioning using rice hull charcoal or ‘serbuk bata merah’ with rhizobacteria Pseudomonas fluorescens PG01 or Bacillus spp.CKD061. The seed treatment increased seedling growth by 120% compared to untreated seed. Based on this experiment, rhizobacteria P.fluorescens PG01 or Bacillus CKD061 integrated with rice hull charcoal or ‘serbuk bata merah’ seed matriconditioning can be used as biological agents in improving seed quality of sorghum. Key words: bio-matriconditioning, rhizobacteria, seed quality, sorghum